Synthesis and biological activities of imidazolium acridines and their silver complexes / Olla H S Sharhan - Olla , H S Sharhan (2020)

(untitled)
In the present study, a series of acridine-based imidazolium ligands were synthesized by the Menshutkin reaction and used for the preparation of the silver complexes. The structures were established using NMR and IR spectroscopy as well as high-resolution mass spectrometry. The purity of the ligands was confirmed by CHN elemental analysis, while energy-dispersive X-ray spectroscopy (EDX) was applied for the silver complexes. In view of the luminescent behaviour of acridine, UV-Vis and fluorescence spectra were recorded for ligands and complexes. However, low water solubility constrains potential application as analytical probe. Preliminary in vitro cytotoxicity screenings were performed using an MTT assay against three cancer and two non-tumorigenic cell lines. All compounds showed low toxicity on normal cell lines, while the anticancer activity varied with the cancer cell lines. The complexes exhibited higher activities than the ligands. Incorporation of aromatic structures at the imidazolium substituent typically enhances the activity. All compounds were evaluated for antioxidant activity by using DPPH and FRAP assays. However, practically the FRAP results indicated low activities compared to the reference compound (ascorbic acid). The antibacterial activity of benzimidazolium-based acridine salts and their complexes was screened against standard strains of Gram-positive and Gram-negative bacteria using the disc diffusion method as well as minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. Most compounds were effective against the tested bacteria, while the complexes exhibited higher activities than the ligands.